Atomic Cation‐Vacancy Engineering of NiFe‐Layered Double Hydroxides for Improved Activity and Stability towards the Oxygen Evolution Reaction. Issue 46 (19th October 2021) - Peng, Lishan; Yang, Na; Yang, Yuqi; Wang, Qing; Xie, Xiaoying; Sun‐Waterhouse, Dongxiao; Shang, Lu; Zhang, Tierui; Waterhouse, Geoffrey I. N.
Abstract: NiFe‐layered double hydroxides (NiFe‐LDH) are among the most active catalysts developed to date for the oxygen evolution reaction (OER) in alkaline media, though their long‐term OER stability remains unsatisfactory. Herein, we reveal that the stability degradation of NiFe‐LDH catalysts during alkaline OER results from a decreased number of active sites and undesirable phase segregation to form NiOOH and FeOOH, with metal dissolution underpinning both of these deactivation mechanisms. Further, we demonstrate that the introduction of cation‐vacancies in the basal plane of NiFe LDH is an effective approach for achieving both high catalyst activity and stability during OER. The strengthened binding energy between the metals and oxygen in the LDH sheets, together with reduced lattice distortions, both realized by the rational introduction of cation vacancies, drastically mitigate metal dissolution from NiFe‐LDH under high oxidation potentials, resulting in the improved long‐term OER stability. In addition, the cation vacancies (especially M 3+ vacancies) accelerate the evolution of surface γ‐(NiFe)OOH phases, thereby boosting the OER activity. The present study highlights that tailoring atomic cation‐vacancies is an important strategy for the development of active and stable OER electrocatalysts. Abstract : Metal dissolution induced by lattice distortions was found to be responsible for the activity degradation of NiFe‐LDH catalysts during alkaline OER. This degradation could be suppressed by introducing atomic cation vacancies in the LDH basal plane. Cation vacancy engineering strengthened the binding energy between metal cations and oxygen in the LDH layers and reduced lattice distortions, thereby enhancing catalyst stability and promoting active phase γ‐(NiFe)OOH evolution during OER.